2017
DOI: 10.1007/s00264-017-3489-z
|View full text |Cite
|
Sign up to set email alerts
|

Painful stress reaction in the posterior subtalar joint after resection of os trigonum or posterior talar process

Abstract: Retrospective case series; Evidence Level 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Posterior ankle impingement syndrome (PAIS) is a condition that commonly presents in people who undertake activities requiring repetitive ankle plantar flexion (13). It can limit participation and is potentially career-threatening in elite populations (4). It manifests as posterior ankle pain with painful movement restriction and subsequent activity limitation (58).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior ankle impingement syndrome (PAIS) is a condition that commonly presents in people who undertake activities requiring repetitive ankle plantar flexion (13). It can limit participation and is potentially career-threatening in elite populations (4). It manifests as posterior ankle pain with painful movement restriction and subsequent activity limitation (58).…”
Section: Introductionmentioning
confidence: 99%
“…PAIS is commonly clinically diagnosed in the context of posterior ankle pain associated with ankle plantar flexion (4,(10)(11)(12)(13)(14)(15). Imaging techniques are frequently employed diagnostically or to guide intervention (13,(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, excessive osteotomy can ensure the elimination of impact symptoms, but it's more traumatic to the ankle, and the corresponding complications may occur due to extensive osteotomy. Frigg et al's research showed that the resection of os trigonum or posterior talar process had a complication rate of 13.3% with persisting inability to do sports due to painful stress reaction in the posterior subtalar joint 11 . The causes of complications were mainly attributed to the following three reasons.…”
Section: Discussionmentioning
confidence: 99%
“…11 The diagnostic clinical test is the passive plantarflexion test. [15][16][17] Imaging is frequently used to confirm the diagnosis, 11 especially when an os trigonum or Stieda process is seen 13,18 ; however, clinical severity is not consistent with xray 19,20 or bone scintigraphy findings. 21 Magnetic resonance imaging (MRI) allows better assessment of the soft tissue and bone marrow of the posterior ankle, 18 and certain MRI findings, such as bone marrow edema, accessory muscles, synovitis, and FHL tendon pathology, have been retrospectively described and implicated in PAIS in symptomatic dancers 3,10 and athletes.…”
Section: Introductionmentioning
confidence: 99%